A High-Risk Profile for Invasive Fungal Infections Is Associated with Altered Nasal Microbiota and Niche Determinants - Costantini, Claudio; Nunzi, Emilia; Spolzino, Angelica; Merli, Francesco; Facchini, Luca; Spadea, Antonio; Melillo, Lorella; Codeluppi, Katia; Marchesi, Francesco; Marchesini, Gessica; Valente, Daniela; Dragonetti, Giulia; et al. (Infection and immunity, 2022)
It is becoming increasingly clear that the communities of microorganisms that populate the surfaces exposed to the external environment, termed microbiota, are key players in the regulation of pathogen-host cross talk affecting the onset as well as the outcome of infectious diseases. We have performed a multicenter, prospective, observational study in which nasal and oropharyngeal swabs were collected for microbiota predicting the risk of invasive fungal infections (IFIs) in patients with hematological malignancies. Here, we demonstrate that the nasal and oropharyngeal microbiota are different, although similar characteristics differentiate high-risk from low-risk samples at both sites. Indeed, similar to previously published results on the oropharyngeal microbiota, high-risk samples in the nose were characterized by low diversity, a loss of beneficial bacteria, and an expansion of potentially pathogenic taxa, in the presence of reduced levels of tryptophan (Trp). At variance with oropharyngeal samples, however, low Trp levels were associated with defective host-derived kynurenine production, suggesting reduced tolerance mechanisms at the nasal mucosal surface. This was accompanied by reduced levels of the chemokine interleukin-8 (IL-8), likely associated with a reduced recruitment of neutrophils and impaired fungal clearance. Thus, the nasal and pharyngeal microbiomes of hematological patients provide complementary information that could improve predictive tools for the risk of IFI in hematological patients.
Keywords: mikrobiota; hematological malignancies; tolerance; nos; nasal microbiome; invazivní mykotické infekce; Nose; Humans; prospektivní studie; Prospective Studies; invasive fungal infection; kynurenine; tryptophan; Microbiota; Bacteria; lidé; Invasive Fungal Infections